Legal Certainty of Criminal Responsibility For Corruption Crime to its Perpetrators with the Strictest Impossion of Sentences - Sari, Nani Widya; Sambas, Nandang; Darusman, Yoyon M (Yayasan Sinergi Kawula Muda, 2024)
This research is purposed to know and understand the legal certainty of criminal liability for perpetrators of criminal acts of corruption? Then also to know and understand what efforts must be made to overcome, prevent and eradicate corruption that has occurred so far. The method used in this research is normative juridical research method conducted by collecting secondary data through literature study. The results of the study indicate that the legal certainty of criminal liability for perpetrators of corruption is that the perpetrators of corruption must be sentenced to the most severe punishment as stated in the provisions of existing laws and regulations as part of legal objectives. Efforts that can be made to overcome, prevent and eradicate corruption are that anyone must uphold ethics and morals in carrying out their duties and responsibilities, especially legal officials and no less important is the community in this case must be willing and brave to report if there are allegations of criminal acts of corruption that occur in their environment. And last but not least, public services must be continuously improved. So that opportunities for corruption can be avoided